Republic of Armenia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2005)
This paper evaluates Armenia's Poverty Reduction Strategy Paper (PRSP) Progress Report covering August 2003-December 2004. The developments in 2003-04 are rather reassuring. The resulting pattern, overall, is more favorable than what was foreseen by the PRSP development scenario. Particularly, the economy grew twice as rapidly as the projected rate, and the government continues to implement a public expenditure policy that is focused on social sectors and infrastructure development. As a result, compared with PRSP targets, a better performance on poverty and inequality reduction has been recorded in 2003.